The Impact of Risk Management on Islamic Bank Performance in Indonesia - Khairul Fatihin, Muh.; Sapwan, Muhammad; Hosfaikoni Hadi, Nizar (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2024)
Risk management gained growing attention in Islamic banking. This study aims to investigate the impact of risk management on the performance of Islamic banks in Indonesia. The risks used are financing risk, market risk, operational risk, liquidity risk, and rate of return risk (ROR). Using the data panel regression, where the method is the best method for data consisting of time series and cross sections. The data is obtained from the financial reports of each Islamic commercial bank. Meanwhile, the sampling technique used is the purposive sampling technique. The result shows that Financing risk, market risk, liquidity risk, and rate of return risk have a significant effect on Islamic bank performance. Overall, financing risk is the most influential risk toward the performance of Islamic banks in Indonesia. The results of this study have important implications for practitioners and regulators. Therefore, Islamic banks need to improve the standards of risk management practices, especially financing risk management.